Stroke: a scoping review - Darwiche, Mustafa (2021)
Stroke is a disease with a high burden of morbidity and mortality nationally and globally. In the United States, it is the fifth leading cause of death, with an overall prevalence of 2.6% in the period between 2009 and 2012. In Brazil, there are an estimated 2,231,000 people with stroke and 568,000 with severe disability. This article seeks to describe characteristics of this acute injury to assist health professionals in finding important information related to this pathology. Risk factors such as hypertension, diabetes, dyslipidemia, atrial fibrillation and carotid stenosis have been associated with increased risk of stroke, with hypertension being the most important. Although clinical signs and symptoms are important, neuroimaging is fundamental to differentiate ischemic stroke from hemorrhagic stroke to guide the most appropriate treatment. Some of the differential diagnoses of stroke are transient ischemic attack (TIA), seizures, headache, hypoglycemia, tumors, vertigo and altered mental status. Some medical complications after stroke are dysphagia, urinary incontinence, pulmonary embolism, deep vein thrombosis (DVT), pneumonia, depression, and pressure ulcers. The correct and early diagnosis of stroke is extremely important to avoid the sequelae of this acute event and the adequate treatment of hypertension, diabetes mellitus and dyslipidemia are of great importance to reduce the high prevalence of stroke.